I assume you mean............
6X + 17 = 0
subtract 17 from both sides
6X + 17 - 17 = - 17
6X = -17
divide both sides by 6
X = -17/6
check
6(-17/6) + 17 = 0
-102/6 + 17 = 0
-17 + 17 = 0
0 = 0
checks
8x-17=6x+112x=28x=14
8x-17=6x+15 8x=6x+32 (added 17 to each side) 2x=32 (subtracted 6x from each side) x=16 (divided each side by 2).
(9,6)
(0,7)
6x plus 3 equals 8x plus 14 when solved mathematically is equal to x = -5.5.
8x-17=6x+112x=28x=14
7x + 9 = 6x + 17 7x - 6x = 17 -9 x = 8
-6x + 12y = -102 -6x = -12y - 102 x = 2y + 17
2x+17=6x-23 23+17=6x-2x 40=4x x=40 / 4 therefore x=10
8x-17=6x+15 8x=6x+32 (added 17 to each side) 2x=32 (subtracted 6x from each side) x=16 (divided each side by 2).
7+10+(-6x)=17-6x
(9,6)
6x+x = 7x
(0,7)
6x plus 3 equals 8x plus 14 when solved mathematically is equal to x = -5.5.
-6x
x=10